O ensino de filosofia na Reforma Gentile (1923- 1925) - Domenici, Marcos Rodrigo (2015)
The objective of this research is to develop a study around the teaching of Philosophy in the Italian secondary schools, based on the education reform fostered by Giovanni Gentile, Ministro della Pubblica Istruzione (Secretary of the Department of Education, in English). We will focus this study during the years of 1923 - 1925, when the reform was implemented, until the moment it suffered some changes promoted by the Secretaries of Education who succeeded Gentile. In order to achieve these objectives, we divided the research into three sections. The first section is to familiarize the reader with the history of this research, which is presenting the first years of the fascist regime implemented by Mussolini. This way, we will discuss the development of the fascism as a myth and investigate its primary impacts in the education and in the Italian society as a whole. The second section will focus on the introduction of the philosopher Giovanni Gentile. It will talk about the application of his education reform in the Italian schools, which had been stagnated since 1859, without significant accomplishments. In the third section, we will cover the teaching of Philosophy, which is present in the secondary schools but excluded from other types of schools, such as technical institutes and complementary schools. This reform has ensured the presence of the teaching of Philosophy in the curriculum but has not been enough to guarantee it to be offered to all Italian youths. The reasons that led to this unequal treatment on the teaching of Philosophy will be reviewed during this research.